1998
DOI: 10.1523/jneurosci.18-09-03426.1998
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Regions of the Periaqueductal Gray Are Involved in the Acquisition and Expression of Defensive Responses

Abstract: In fear conditioning, a rat is placed in a distinct environment and delivered footshock. The response to the footshock itself is called an activity burst and includes running, jumping, and vocalization. The fear conditioned to the distinct environment by the footshock elicits complete immobility termed freezing. Lesions of the ventral periaqueductal gray (vPAG) strongly attenuate freezing. However, lesions of the dorsolateral periaqueductal gray (dlPAG) increase the amount of freezing seen to conditional fear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
158
0
6

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(175 citation statements)
references
References 39 publications
11
158
0
6
Order By: Relevance
“…A role for the PAG in mediating fear and anxiety has also been well documented (Bandler and Shipley, 1994;Blanchard et al, 1981;DeOca et al, 1998) and SP neurotransmission has been implicated here as well (De Araujo et al, 1999;Gregg and Siegel, 2003;Mongeau et al, 1998). The findings of our study support a critical role of SP neurotransmission within the PAG in fear-potentiated startle and indicate more specifically that these effects may be mediated primarily by SP receptors in the rostral dlPAG.…”
Section: Discussionsupporting
confidence: 83%
“…A role for the PAG in mediating fear and anxiety has also been well documented (Bandler and Shipley, 1994;Blanchard et al, 1981;DeOca et al, 1998) and SP neurotransmission has been implicated here as well (De Araujo et al, 1999;Gregg and Siegel, 2003;Mongeau et al, 1998). The findings of our study support a critical role of SP neurotransmission within the PAG in fear-potentiated startle and indicate more specifically that these effects may be mediated primarily by SP receptors in the rostral dlPAG.…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, these mutants perform normally in the immediate STFP task, a hippocampal-independent task. Because the mechanisms for production of the freezing response for contextual and cued fear conditioning are similar (43,47,48), it is unlikely that Syt IV mutants exhibited deficits in freezing per se. For example, after context overtraining, Syt IV mutants exhibited freezing comparable to that of wild-type animals (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has all the anatomical connectivities one would expect of a major emotion system integrator [7,15,27,61] and it exhibits functional changes as a result of emotional arousal [1,4,6,36]. Electrical and chemical stimulation of the PAG produces defensive and freezing behaviors in the rat [3,30] and many studies have shown that distinct regions of the PAG are involved in the acquisition and expression of various defensive behaviors [19,34]. Dramatic increases in transcriptional activity in the PAG during dominant/submissive encounters have been observed.…”
Section: Introductionmentioning
confidence: 99%